2017
DOI: 10.1080/03639045.2017.1371736
|View full text |Cite
|
Sign up to set email alerts
|

Formulation for a novel inhaled peptide therapeutic for idiopathic pulmonary fibrosis

Abstract: A caveolin-1 scaffolding domain, CSP7, is a newly developed peptide for the treatment of idiopathic pulmonary fibrosis. To develop a CSP7 formulation for further use we have obtained, characterized and compared a number of lyophilized formulations of CSP7 trifluoroacetate with DPBS and in combination with excipients (mannitol and lactose at molar ratios 1:5, 70 and 140). CSP7 trifluoroacetate was stable (>95%) in solution at 5 and 25°C for up to 48 hours and tolerated at least 5 freeze/thaw cycles. Lyophilized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 66 publications
(88 reference statements)
2
3
1
Order By: Relevance
“…Various counterions also affect the stability of CSP7 in solution. Hengsawas et al previously reported that CSP7 TFA was stable after 24 h of shaking on an orbital shaker at 5 °C and 25 °C [22]. However, we found that CSP7 acetate was also physically unstable after 6 h of shaking on an orbital shaker at 5 °C and 25 °C.…”
Section: Discussioncontrasting
confidence: 50%
See 4 more Smart Citations
“…Various counterions also affect the stability of CSP7 in solution. Hengsawas et al previously reported that CSP7 TFA was stable after 24 h of shaking on an orbital shaker at 5 °C and 25 °C [22]. However, we found that CSP7 acetate was also physically unstable after 6 h of shaking on an orbital shaker at 5 °C and 25 °C.…”
Section: Discussioncontrasting
confidence: 50%
“…The effect of various counterions on the stability of CSP7 was also compared with the results from the previous study. Hengsawas et al reported that Formulation 5 was chemically and physically stable after one month of storage at 25 °C and 60% RH [22]. We found that lyophilization did not affect the presence of TFA counterions.…”
Section: Discussionsupporting
confidence: 46%
See 3 more Smart Citations